Nifedipine Potentiates Susceptibility of Salmonella Typhimurium to Different Classes of Antibiotics - David Haschka; Manuel Grander; Johannes Eibensteiner; Stefanie Dichtl; Sabine Koppelstätter; Günter Weiss (MDPI AG, 2021)
The calcium channel blocker nifedipine induces cellular iron export, thereby limiting the availability of the essential nutrient iron for intracellular pathogens, resulting in bacteriostatic activity. To study if nifedipine may exert a synergistic anti-microbial activity when combined with antibiotics, we used the mouse macrophage cell line RAW267.4, infected with the intracellular bacterium Salmonella Typhimurium, and exposed the cells to varying concentrations of nifedipine and/or ampicillin, azithromycin and ceftriaxone. We observed a significant additive effect of nifedipine in combination with various antibiotics, which was not observed when using Salmonella, with defects in iron uptake. Of interest, increasing intracellular iron levels increased the bacterial resistance to treatment with antibiotics or nifedipine or their combination. We further showed that nifedipine increases the expression of the siderophore-binding peptide lipocalin-2 and promotes iron storage within ferritin, where the metal is less accessible for bacteria. Our data provide evidence for an additive effect of nifedipine with conventional antibiotics against Salmonella, which is partly linked to reduced bacterial access to iron.